Training for Making Interactive Learning Media Based on Open Broadcaster Software (OBS) Studio for State State School Teachers Inpres Ardipura 1 Kota Jayapura - Yasir Attamimi; Johanis R. Wanma (Ridwan Institute, 2022)
On March 2, 2020, the Unitary State of the Republic of Indonesia experienced a coronavirus disease 2019 (COVID-19) outbreak with the coronavirus disease 2019 (COVID-19) outbreak, resulting in a shift in learning practices that were previously carried out conventionally to become digital. Simultaneously, this shift from conventional to digital learning practices forces a teacher to quickly adapt and use digital technology to remain able to provide optimal educational services and not be reduced in terms of the quality of education. It is the adaptation of a teacher to digital technology which in practice in the field there are still shortcomings due to the presence of several limitations such as lack of facilities or lack of teacher competence in developing interactive learning media, which has resulted in not all teachers being able to implement online teaching and learning activities due to limitations. The. During a pandemic like this, the ability of teachers to use learning media by utilizing digital technology is essential, one of the learning applications that is currently being used as a tool for making learning materials in Indonesia is the Open Broadcaster Software (OBS) studio application which is an application video recording and live streaming that can help a teacher in making learning materials in the form of video recordings. The use of this application is very useful so that teachers can continue to provide lecture material effectively and efficiently. The implementation of the training on making interactive learning media based on Open Broadcaster Software (OBS) studio for elementary school teachers in the city of Jayapura, Inpres Ardipura 1, begins with the process of preparing for the implementation of activities after that, planning activities and training for the introduction of Open Broadcaster Software (OBS) studio in which the team will introduce the Open Broadcaster Software (OBS) studio application as a whole, starting with how to download the application, install the application, application functions to all the features contained in the application with the expected end result that all trainees can use this application. After that, then proceed to the practice of making interactive learning materials based on the Open Broadcaster Software (OBS) studio, at this stage, all participants will directly make video recordings using the Open Broadcaster Software (OBS) studio application